A study on the factors affecting employees' performance in Northern Malaysia Commercial Bank / Norhidayah Ayob and Fatin Nur Athirah Ibrahim - Ayob, Norhidayah; Ibrahim, Fatin Nur Athirah (2018)
Employees' performance is the root of organization's success. Poor performance will cause failure in achieving organizational goal while good performance will make an organization success in every industry. However, there are many barriers to the performance. This chapter focuses on the factors affecting employees' performance in Northern Malaysia Commercial Bank. Therefore, this study represents the factors affecting employees' performance where the highlight is on four factors which are working environment, motivation, empowerment, and teamwork. Based on the finding in this study, the results revealed that these four factors are accepted as the contributing factors of employees' performance. Hence, motivation ts seen of the main factor of employees' performance in northern Malaysia commercial bank.